Music Therapy for People with Intellectual Disabilities: Stigma Intervention Strategies - Baranauskienė, Ingrida; Latakienė, Jurgita (Special Education, 2023)
The research presented in the article aims to justify the application of the method of music therapy in the long-term perspective of the social worker’s professionalization for people with intellectual disabilities. The object of the research is the impact of music therapy on persons with intellectual disabilities as a stigma research & intervention strategy in the context of the professionalization of social work. The aim of the article is to reveal the impact of music therapy on persons with intellectual disabilities in the context of the professionalization of social work. The object of the research was delved into from various angles in order to answer the research questions: How useful is music therapy for people with intellectual disabilities in the context of social work striving to overcome stigma and choosing music therapy as a strategy? How useful is the authorial research methodology developed by the researchers for the application of music therapy for the quality of life of people with intellectual disabilities in the context of social assistance and in overcoming systems barriers? To what extent are the research participants able to express their feelings and evaluate the process of music therapy, to influence the social worker’s activities related to music therapy? To what extent and how does such activity expand the boundaries of the social worker’s profession and in what direction does it change professional standards? Data analysis proves that music therapy helps people with intellectual disabilities and society to overcome stigma. Referring to the research findings it can be stated that the authorial methodology for the application of music therapy created by the researchers in order to achieve the quality of life of people with intellectual disabilities in the context of social assistance is effective and can be implemented in practice to overcome the systems barriers.